2012
DOI: 10.1007/s00246-012-0219-6
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic Diet: Rapid Onset of Selenium Deficiency-Induced Cardiac Decompensation

Abstract: Selenium-deficiency cardiomyopathy is a known secondary complication from long-term treatment with a ketogenic diet for medical refractory epilepsy. Our patient, a 5-year-old boy on a ketogenic diet for intractable seizures, had a normal selenium level before starting the diet, but he shortly thereafter developed acute reversible cardiomyopathy and ventricular tachycardia, which was unmasked during a hospitalization for an elective operative procedure. His cardiomyopathy was suspected to be secondary to a sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 13 publications
0
23
0
2
Order By: Relevance
“…The long-term use of the ketogenic diet in children with refractory seizure disorders is a risk factor of selenium-associated cardiomyopathy. Selenium supplements and the cessation of a ketogenic diet can reverse this cardiomyopathy [215]. …”
Section: Nutritional Status Of Children With Cardiomyopathymentioning
confidence: 99%
“…The long-term use of the ketogenic diet in children with refractory seizure disorders is a risk factor of selenium-associated cardiomyopathy. Selenium supplements and the cessation of a ketogenic diet can reverse this cardiomyopathy [215]. …”
Section: Nutritional Status Of Children With Cardiomyopathymentioning
confidence: 99%
“…Individuals following a KD have been shown to have reduced serum 25‐hydroxyvitamin D concentration (as were individuals solely on antiepileptic drugs) and reduced bone mass (to a greater extent than in individuals solely on drug therapy); another study found 25‐hydroxyvitamin D levels (which were mostly low at diet initiation) to improve initially on commencement of a KD, including supplementation, but to decline after three months . Selenium deficiency has been reported in 66 individuals on KD treatment, associated with cardiomyopathy in two of these patients and sudden cardiac death in another two . A trend of decreasing plasma selenium was noted in participants of the original randomized controlled trial at GOSH, with a significant decrease between baseline and six months in children on the classical KD, although mean plasma selenium was maintained within the GOSH reference ranges …”
Section: Discussionmentioning
confidence: 99%
“…Aunque es infrecuente, por su gravedad, es indispensable la evaluación cardiológica periódica. [24][25][26] Con respecto al efecto que la dieta ejerce sobre el crecimiento, los últimos reportes indican que, con aporte calórico y proteico adecuados, se logra un ritmo de crecimiento normal. 27,28 En cada consulta, los datos de antropometría se evalúan y comparan con los patrones de crecimiento recomendados por la Sociedad Argentina de Pediatría.…”
Section: Efectos Adversos a Corto Y Largo Plazounclassified